ANALYSIS OF POEMS ("Conference on Universal Science Research 2023", 2023)
This article gives information about analysis of poems. In this article it has several paragraphs, which give full data about this. Stylistic analysis in literary studies often involves interpreting the layers of a text through close reading rather than through plot.  It takes inner thoughts and reveals them with logical descriptions such as point of view, setting, images, symbols, tone, atmosphere, personification. In this article, candidates can learn how to be a good learner and what is analysis of poems. And candidates can learn how to use it?